2019
DOI: 10.1159/000496558
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Structural Parameters of the Lamina Cribrosa in Primary Open-Angle Glaucoma and Chronic Primary Angle-Closure Glaucoma by Optical Coherence Tomography and Its Correlations with Ocular Parameters

Abstract: Purpose: To measure lamina cribrosa thickness (LCT) and anterior lamina cribrosa surface depth (ALCSD) in primary open-angle glaucoma (POAG), chronic primary angle-closure glaucoma (CPACG), and control patients using spectral-domain optical coherence tomography (SD-OCT) and examine its association with relevant ocular parameters. Methods: In this cross-sectional study, 61 healthy volunteers (61 eyes), 65 POAG patients (65 eyes), and 55 CPACG patients (55 eyes) were recruited to obtain radial B-scans of the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In our study cases revealed significant LC thinning as compared to controls, and similar results have also been proposed by Hao et al 16 in which LC thinning had been detected in POAG and primary angle closure glaucoma patients. Park et al also expounded that LC irregularities correlate with the RNFL thinning in POAG subjects.…”
Section: Visual Field Defects In Primary Open Angle Glaucomasupporting
confidence: 92%
“…In our study cases revealed significant LC thinning as compared to controls, and similar results have also been proposed by Hao et al 16 in which LC thinning had been detected in POAG and primary angle closure glaucoma patients. Park et al also expounded that LC irregularities correlate with the RNFL thinning in POAG subjects.…”
Section: Visual Field Defects In Primary Open Angle Glaucomasupporting
confidence: 92%
“…The inclusion criteria for all subjects were (1) a diagnosis of advanced primary open-angle glaucoma (POAG) or chronic primary angle-closure glaucoma (CPACG) based on a 24-2 VF MD of ≤−12 dB, (2) age ≥18 years, (3) a BCVA of at least 20/50, and (4) a spherical refraction of −6.0 to +3.0 diopters and cylinder correction within ±3.0 diopters. POAG was diagnosed in patients with a glaucomatous VF defect in 2 consecutive reliable VF examinations, typical glaucomatous optic neuropathy (i.e., neuroretinal rim thinning, notching, or an RNFL defect), open angles on gonioscopy, and a confirmed untreated IOP >21 mm Hg [32, 33]. Glaucomatous VF defects were defined as a cluster of 3 or more nonedge contiguous points on a pattern deviation plot at the p < 5% level (with at least 1 point depressed at the p < 1% level) confirmed in at least 2 consecutive examinations, a pattern standard deviation (PSD) at the p < 5% level, or a glaucoma hemifield test result outside normal limits [34].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effect of changes in LC and consequently TLPG, it was reported that in eyes with glaucoma, a deeper and thinner LC (which increases TLPG) is associated with a thinner retinal nerve ber layer (RNFL, which consists of RGCs and their axons). 12,36 Another study stated a signi cant association between thinner LC and a faster rate of RNFL thinning in primary open-angle glaucoma. 37 The effects of SO on retinal layers have been investigated in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 LC thinning and posterior displacement are considered to be associated with optic neuropathy and subsequent visual impairment via the disruption of axoplasmic ow within the optic nerve. [10][11][12][13] In this study, our objective is to investigate changes in thickness and depth of LC in patients who underwent pars plana vitrectomy (PPV) and received SO as the treatment method compared to their fellow eyes.…”
Section: Introductionmentioning
confidence: 99%